The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12870-021-02886-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and accumulation of amylase-trypsin inhibitors and changes in carbohydrate profile during grain development of bread wheat (Triticum aestivum L.)

Abstract: Background Recent studies indicate that amylase-trypsin inhibitors (ATIs) and certain carbohydrates referred to as FODMAPs (fermentable oligo-, di-, monosaccharides and polyols) play an important role in promoting wheat sensitivity. Hitherto, no study has investigated the accumulation of ATIs during the development of the wheat caryopsis. We collected caryopses of common wheat cv. ‘Arnold’ at eight different grain developmental stages to study compositional changes in ATI and FODMAP content. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Amylase trypsin inhibitors were detected and quantified in a wide range of wheat cultivars via discovery proteomics and data mining by Bose et al. (2020) and the synthesis and accumulation of amylase-trypsin inhibitors during grain development of bread wheat has been documented by Call et al. (2021) .…”
Section: Influential Factors and Biomarkers For Gut Integritymentioning
confidence: 99%
“…Amylase trypsin inhibitors were detected and quantified in a wide range of wheat cultivars via discovery proteomics and data mining by Bose et al. (2020) and the synthesis and accumulation of amylase-trypsin inhibitors during grain development of bread wheat has been documented by Call et al. (2021) .…”
Section: Influential Factors and Biomarkers For Gut Integritymentioning
confidence: 99%
“…In wheat the more prominent ones are 0.28 (monomeric), 0.19 and 0.53 (both homodimeric) (named based on electrophoretic mobility), CM1, CM2, CM3, CM16 and CM17 (all heterotetrameric) (for names and numbering see Rodriguez-Loperena et al, 1975;Carbonero and Garcia-Olmedo, 1999;Geisslitz et al, 2021). A time lag between ATI accumulation during wheat grain filling and detection of the biological activity suggested that assembly into dimers and tetramers determined the inhibitory potential (Call et al, 2021). Nineteen ATI isoforms from the wheat cultivar Butte 86 (Altenbach et al, 2011) and 33 proteoforms of ATIs across different bread wheat cultivars are reported (Bose et al, 2020;Geisslitz et al, 2021).…”
Section: General Characteristics Occurrence and Phylogeny Of Cm-proteinsmentioning
confidence: 99%
“…One was the tandem mass spectrometric analysis of known ATIs to identify/quantify their amounts in cereal products. [16][17][18][19][20][21][22][23][24][25] The other approach was the screening of the ATI inhibitory potency via enzymatic assays followed by non-selective spectrophotometric detection. 7,23,24,26 However, mass spectrometry and enzymatic assays were rarely combined for an ideal matching, difficult to interpret, 24 and recently no correlation between ATI amount and inhibition potential was found.…”
Section: Introductionmentioning
confidence: 99%